Metabolome combined with gut microbiome revealed the lipid-lowering mechanism of Xuezhiping capsule on hyperlipidemic hamster induced by high fat diet - Wang, Li; Zhang, Zhixin; Luo, Gan; Wang, Ying; Du, Ke; Gao, Xiaoyan (Frontiers in Molecular Biosciences, 2023)
Hyperlipidemia is a common metabolic disorder with presence of excess fat or lipids in the blood, may induce liver injury, oxidative stress and inflammatory. Xuezhiping capsule (XZP) is a famous Chinese patent medicine clinically used for anti-hyperlipidemia. However, the regulation mechanism of XZP on hyperlipidemia has not been elucidated so far. This study aimed to explore the effects of XZP on hypolipidemic, antioxidant and anti-inflammatory effects, and the potential mechanism by a combination of untargeted metabolomics and 16S rRNA sequencing. The results indicated that XZP reduced the level of total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C), increased the level of high density liptein cholesterol (HDL-C), alleviated excessive accumulation of lipid droplets in liver. Biochemical indexes of liver function including gamma glutamyl transferase (GGT) and glutamic oxaloacetic transaminase (GOT) in liver were remarkably decreased. Meanwhile, XZP increased the level of oxidative stress biochemical indexes including superoxide dismutase (SOD) and glutathione (GSH). In addition, XZP increased the level of peroxisome proliferators-activated receptors α (PPARα), acetyl CoA carboxylase 1 (ACOX1) and cholesterol 7-alpha hydroxylase (CYP7A1) in liver, and improved lipid metabolism in serum, liver and fecal lipid metabolism. XZP increased diversity index and the ratio of Firmicutes and Bacteroidetes, regulated seventeen genera, and illustrated strong correlations with liver lipid metabolism and phenotypic indicators. These findings suggest that XZP reduced blood lipid and liver lipid, protected liver function, anti inflammation and anti-oxidation, ameliorate lipid metabolic disorders by modulating alpha linolenic acid and linoleic acid metabolism, bile acid metabolism, arachidonic acid metabolism, and regulated gut microbiota composition of high-fat diet (HFD) hamsters.